From wallets to screens: Exploring the determinants of QRIS payment adoption among Millennials in Eastern Indonesia - Tatian, Calysta Tartila; Nurabiah, Nurabiah; Ridhawati, Rini; Thao, Hoang Thi Phuong (University of Islam Malang, 2024)
In response to the global challenges and the demands of the digital revolution, Bank Indonesia launched the Quick Response Code Indonesian Standard (QRIS), a unified payment system designed to enhance convenience and security. Despite these potential benefits, the adoption rate of QRIS has been relatively slow. This study aims to understand the factors driving the adoption of QRIS among Millennials in Eastern Indonesia by examining how attitudes, subjective norms, and perceived behavioral control affect their intention to use QRIS. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), we analyzed data from 505 respondents. The findings reveal that attitudes, subjective norms, and perceived behavioral control significantly impact Eastern Indonesian Millennials intention to adopt QRIS. Interestingly, even though Eastern Indonesia is known for its inadequate digital infrastructure and low digital literacy, these internal behavioral factors are remarkably positive. This indicates that the low penetration of QRIS in the region is mostly due to external factors rather than individual behavioral tendencies.